4(2x-3)+7=x+5+x

Simple and best practice solution for 4(2x-3)+7=x+5+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-3)+7=x+5+x equation:


4 (2x-3)+7=x+5+x

We simplify the equation to the form, which is simple to understand
4(2x-3)+7=x+5+x

Reorder the terms in parentheses
+(+8x-12)+7=x+5+x

Remove unnecessary parentheses
+8x-12+7=+x+5+x

We move all terms containing x to the left and all other terms to the right.
+8x-1x-1x=+5+12-7

We simplify left and right side of the equation.
+6x=+10

We divide both sides of the equation by 6 to get x.
x=1.6666666666667

See similar equations:

| -4(5x+10)=-180 | | 0=12x^2-4x^3 | | 11+17-6x=2 | | 3x+14=94 | | 2x^2+4+5x=4 | | 4-3t+10+10t=0 | | x-(-28)=-48 | | -5(1+a)-6a=-8a+19 | | x-6=15+8x | | 0=24x-12x^2 | | 3x+5x-3=8x | | -3x-184=59-12x | | -56+h-8= | | 2.4=(m+4) | | -7(2+2x)=-70 | | 4x+3(-2x-7)=-7 | | 7a+10a+7a+12a=360 | | -(9-5n)= | | -2(4+m)+6(m-3)=14 | | 4(5x-4)+10=-3 | | 20+8(11-q)=-12 | | 240=126-v | | 6x-12x+9=-27 | | -24-5x=-4(x+5) | | y=101.21x+0.0991 | | 2(3*-0.5+2)-2*-0.5=6*-0.5+5 | | 3(4j-3)8=-1+12j | | 12a+99a=3885 | | -11u-6=3u^2 | | 32-8p=-8(4p+2) | | 7+x=8x-2 | | -7-3v-10+3v=0 |

Equations solver categories